2019
DOI: 10.3389/fimmu.2019.01046
|View full text |Cite
|
Sign up to set email alerts
|

B-Cell Activating Factor Predicts Acute Rejection Risk in Kidney Transplant Recipients: A 6-Month Follow-Up Study

Abstract: B cell activating factor (BAFF) belonging to TNF family is a cytokine that enhances B-cell proliferation and differentiation. Recently, It has been suggested that BAFF might be a potential therapeutic target for treating autoimmune disease. However, the relationship between BAFF and allograft rejection is controversial, and the clinical significance of BAFF in predicting allograft rejection need to be further explored. We conducted 6-month follow-up study to confirm the hypothesis that BAFF might be a risk fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Unlike the results showed by different groups where no differences were found in BAFF levels between kidney transplant recipients and controls [31] indicating that this molecule is not a prognostic marker for allograft dysfunction, or that no correlation exists between BAFF and the production of DSA before and after transplantation [32], in the present study we observed that patients with AbMR presented higher levels of BAFF before transplantation, being also elevated BAFF serum levels in those patients with anti-HLA antibodies and DSA. These results are in a relationship published by other authors showing that BAFF is associated with allograft survival [37], acute antibody-mediated rejection as well as the presence of DSA [28,29,38]. A meta-analysis published recently also corroborates our results, indicating that the incidence of antibody-mediated rejection is higher in those patients with higher levels of serum BAFF.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Unlike the results showed by different groups where no differences were found in BAFF levels between kidney transplant recipients and controls [31] indicating that this molecule is not a prognostic marker for allograft dysfunction, or that no correlation exists between BAFF and the production of DSA before and after transplantation [32], in the present study we observed that patients with AbMR presented higher levels of BAFF before transplantation, being also elevated BAFF serum levels in those patients with anti-HLA antibodies and DSA. These results are in a relationship published by other authors showing that BAFF is associated with allograft survival [37], acute antibody-mediated rejection as well as the presence of DSA [28,29,38]. A meta-analysis published recently also corroborates our results, indicating that the incidence of antibody-mediated rejection is higher in those patients with higher levels of serum BAFF.…”
Section: Discussionsupporting
confidence: 92%
“…We also observed that serum BAFF levels, measured at 6 and at 12 months after transplantation were also higher in those patients with subclinical antibody-mediated rejection detected in the surveillance biopsy, corroborating the possible contribution of BAFF to the pathogenesis of antibody-mediated graft damage. Considering this aspect, Won Min et al described that while pretransplant BAFF levels showed significant association with early rejection, posttransplant BAFF levels measured at the time of indication biopsy are not associated with allograft rejection [25].It is important to highlight some relevant aspects of our study such as the prospective monitoring of the kidney transplant patients at 6 and at 12 months after kidney transplantation, which differentiates it from other transversal studies or with a shorter period of follow-up [28,29]. In the same way we would like to emphasize the importance of surveillance biopsy that gives up data about the possible existence of a subclinical rejection.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…2f). TNFR13B encodes TACI, a receptor for BAFF overexpression of which is associated with renal allograft rejection 31,32 .…”
Section: Resultsmentioning
confidence: 99%
“…BAFF mediates B cell survival and is important in some B-cell-mediated inflammatory diseases (Davidson, 2010). Furthermore, BAFF over-expression is associated with renal allograft rejection (Pongpirul et al, 2018;Wang et al, 2019). Therefore, the high expression of TACI in intrarenal B cells suggests a role in in situ activation and survival.…”
Section: Distinct Transcriptional States In Activated Intrarenal and mentioning
confidence: 99%